Evolution of a genomic regulatory domain: The role of gene co-option and gene duplication in the Enhancer of split complex - Duncan, Elizabeth J.; Dearden, Peter K. (Genome Research, 2010)
The Drosophila Enhancer of split complex [E(spl)-C] is a remarkable complex of genes many of which are effectors or modulators of Notch signaling. The complex contains different classes of genes including four bearded genes and seven basic helix-loop-helix (bHLH) genes. We examined the evolution of this unusual complex by identifying bearded and bHLH genes in the genome sequences of Arthropods. We find that a four-gene E(spl)-C, containing three bHLH genes and one bearded gene, is an ancient component of the genomes of Crustacea and Insects. The complex is well conserved in insects but is highly modified in Drosophila, where two of the ancestral genes of the complex are missing, and the remaining two have been duplicated multiple times. Through examining the expression of E(spl)-C genes in honeybees, aphids, and Drosophila, we determined that the complex ancestrally had a role in Notch signaling. The expression patterns of genes found inserted into the complex in some insects, or that of ancestral E(spl)-C genes that have moved out of the complex, imply that the E(spl)-C is a genomic domain regulated as a whole by Notch signaling. We hypothesize that the E(spl)-C is a Notch-regulated genomic domain conserved in Arthropod genomes for around 420 million years. We discuss the consequence of this conserved domain for the recruitment of novel genes into the Notch signaling cascade.